2018
DOI: 10.1163/15685373-12340035
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Differences in Informal Argumentation: Norms, Inductive Biases and Evidentiality

Abstract: Cross-cultural differences in argumentation may be explained by the use of different norms of reasoning. However, some norms derive from, presumably universal, mathematical laws. This inconsistency can be resolved, by considering that some norms of argumentation, like Bayes theorem, are mathematical functions. Systematic variation in the inputs may produce culture-dependent inductive biases although the function remains invariant. This hypothesis was tested by fitting a Bayesian model to data on informal argum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Hahn & Oaksford (2007) argue that in typical real-world settings Pr(C|a) > Pr(¬C|¬a), and consequently, positive arguments should be perceived as stronger than negative arguments. This prediction, and people's sensitivity to priors and likelihoods, has been confirmed experimentally (Hahn & Oaksford 2007, Hahn et al 2005, Oaksford & Hahn 2004) and replicated across cultures (Karaaslan et al 2018).…”
Section: Bayesian Approaches To the Fallacies Of Informal Argumentmentioning
confidence: 63%
See 1 more Smart Citation
“…Hahn & Oaksford (2007) argue that in typical real-world settings Pr(C|a) > Pr(¬C|¬a), and consequently, positive arguments should be perceived as stronger than negative arguments. This prediction, and people's sensitivity to priors and likelihoods, has been confirmed experimentally (Hahn & Oaksford 2007, Hahn et al 2005, Oaksford & Hahn 2004) and replicated across cultures (Karaaslan et al 2018).…”
Section: Bayesian Approaches To the Fallacies Of Informal Argumentmentioning
confidence: 63%
“…The probability that a source is reliable, Pr(R), can be factored into the likelihoods in Bayes' theorem [e.g., Pr(a|C) becomes Pr(a|C, R)Pr(R) + Pr(a|C, ¬R)(1 -Pr(R)], which caps argument strength (Bovens & Hartmann 2003). Manipulating source reliability has predictable effects on the strength of arguments from ignorance; higher reliability leads to greater argument force and hence stronger conclusion endorsement (Hahn & Oaksford 2007, Karaaslan et al 2018.…”
Section: Bayesian Approaches To the Fallacies Of Informal Argumentmentioning
confidence: 99%
“…5There is empirical work emerging on evidentiality in the psychology of reasoning, for example, Krzyżanowska, Wenmackers, and Douven (2013) and Karaslaan, Hohenberger, Demir, Hall, and Oaksford (in press).…”
mentioning
confidence: 99%
“…We note that in related work on Bayesian models of deductive reasoning (Oaksford et al, 2000; Vance & Oaksford, 2021) and informal argumentation (Karaslaan et al, 2018), model-fitting at the individual level has revealed interesting individual variations in reasoning processes. Vance and Oaksford (2021), for example, found their Bayesian model gave a good account of conditional inference with text arguments in a majority of participants who understood the conditional probabilities of events described in those arguments.…”
Section: How Sensitive Are Individuals To Sampling Frames?mentioning
confidence: 84%